The perceptions and experiences of related professionals on the role of the social worker in early childhood development - Trueman, Jade Valentina (My University, 2021)
functionality within each individual child. Early Childhood Development has been a growing area of focus, a priority and developmental goal in South Africa. The democratic South Africa plans on enabling all children between birth and six years of age in the country to achieve long-term sustainability in terms of the National Development Plan 2030. This study aimed to identify phenomena and comprehensive descriptions of the role of the Early Childhood Development Social Worker in South Africa. The qualitative approach and phenomenological design were used as the research methodology to explore the roles of this particular social worker. The research process included the purposive sampling method, where a population group of 17 Early Childhood Development related professionals were identified. The related professionals included: Early Childhood Development Practitioners, Social Workers, Academics and Social Policy Writers. The research instrument used was an in-depth semi-structured interview schedule, which enabled the successive data collection and analysis process. The six-phased thematic analysis method effectively exposed the understanding of the perceptual and experiential roles of the social worker in the Early Childhood Development sector. The overall presentation and discussion of the findings provided an investigation into the identification and reality of the perceptions on the role of the social worker. It was found that while social workers are responsible for informing and guiding human rights processes regarding the child, that this is often lost in the ambiguity of the role and the sector. The key findings, conclusion and recommendations suggest the crucial need to document, critique and formalise the perceptions on the role of the Early Childhood Development Social Worker in South Africa.
A dissertation submitted in partial fulfilment of the requirements for the degree Master of Arts in Social Work to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021